2022
DOI: 10.1167/iovs.63.3.26
|View full text |Cite
|
Sign up to set email alerts
|

RNA Sequencing of Lens Capsular Epithelium Implicates Novel Pathways in Pseudoexfoliation Syndrome

Abstract: Purpose Pseudoexfoliation syndrome (PEX) is a common systemic disease that results in severe and often irreversible vision loss. Despite considerable research effort, PEX remains incompletely understood. This study sought to perform the first RNAseq study in elucidate the pathophysiology of PEX, and contribute a publicly available transcriptomic data resource for future research. Methods Human ocular lens capsular epithelium samples were collected from 25 patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 75 publications
(84 reference statements)
3
8
0
Order By: Relevance
“…Our analysis showed that several XFM components were upregulated in response to TGF-β1 in normal HTM tissue, see Figure 4 . A recently published summary of genes known to be expressed in XFM was used to create a gene list [ 4 ]. Genes that appeared to be upregulated with high significance (FDR < 0.05) were VCAN, ELN, LTBP2, ADAM19, LDHA, FBN1, while MYL6, MYH9 and LOXL1 were also upregulated based on their p -value.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Our analysis showed that several XFM components were upregulated in response to TGF-β1 in normal HTM tissue, see Figure 4 . A recently published summary of genes known to be expressed in XFM was used to create a gene list [ 4 ]. Genes that appeared to be upregulated with high significance (FDR < 0.05) were VCAN, ELN, LTBP2, ADAM19, LDHA, FBN1, while MYL6, MYH9 and LOXL1 were also upregulated based on their p -value.…”
Section: Resultsmentioning
confidence: 99%
“…Stimulation of normal HTM cells with TGF-β1 modulates pathways and biological processes that show much overlap with processes known to be associated with XFG such as ECM remodelling [ 38 , 39 ], modulation of oxidative stress [ 6 ], UPR [ 40 ] and changes in the expression of certain growth factors [ 14 , 41 , 42 ]. Based on these overlapping findings with XFG expression studies [ 4 , 18 , 43 ] the proposed cellular model could be a useful tool to gain more insight in the pathogenesis of XFG which is still poorly understood [ 1 , 2 , 3 , 44 ]. A comparison of relevant pathways and biological processes between this study and literature is discussed in more detail below.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations